Teacher Resilience in Remote Islands Area: A Case Study in Small Pagerungan Island Sumenep Regency, Indonesia - Nurwidodo Nurwidodo; Abdulkadir Rahardjanto; Husamah Husamah; Mas'odi Mas'odi; Arina Mufrihah (Intelektual Pustaka Media Utama, 2017)
This study aims to describe resilience teacher at Elementary school III at Small Pagerungan Island. Aspects of resilience in this study are phase of resilience refers to Patterson and Kelleher (2005) and the strategy of resilience refers to Diah and Pradna (2012). This type of research is descriptive qualitative with case study approach. The subjects were 5 teachers (Subject I: government employee (PNS) teachers senior and immigrant from Java, Subject II: government employee (PNS) teachers senior natives, subject III: temporary teacher who has taught more than 10 years, Subject IV: new civil servant teachers a few years removed, and subject V: new no permanent teachers who teach less than 5 years). Data collected through in-depth interviews with each subject of study. Analysis of data using thematic analysis approach hybrid refers to Fereday and Muir-Cochrane version. The results showed that the phase of resilience to be taken by each teacher is different. Subjects I and II has reached growing phase. Subject IV and V are still at the stage of deteriorating phase, while the subject III only at adapting phase. Subjects I and II have an optimistic view and gave rise to 7 points strategy of resilience, which is a positive attitude to face difficulties, focusing on the core value, versatile in the running for the purpose, willing to take concrete steps to face difficulties, create conditions of self and supportive environment, maintain hope and expectation is high, and develop an attitude of participation and responsibility. Subject IV and V are relatively more optimistic, but because the teaching experience is still limited cause-point strategy of resilience that appears only reached 4, which is flexible in an effort to achieve goals, create conditions of self and supportive environment, maintain hope and expectation is high, and develop an attitude of participation and responsibility. Subject III is more pessimistic and pragmatic look at the future of the profession so that a strategy of resilience that comes only three, namely flexible in an effort to achieve the goal, to create the conditions themselves and a supportive environment, and develop an attitude of participation and responsibility. Point’s resilience strategy that appears, consciously or not by the fifth subject, has been assisting survive to teach at Elementary school III Small Pagerungan Island belonging to the category of remote schools, schools with limited resources, and minimal attention from government.